Recent Booh By Academy Members: Strategic Factors in Business SuccessFinancial Executives Research Foundation, New York, 1969 (117 pp., $3) - Steiner, George A. (Academy of Management Journal, 1969)
The article reviews the book ?Strategic Factors in Business Success,? by George A. Steiner.